Effects of photodynamic exposure using chlorine E6 on U251 glioblastoma cell line in vitro - Rozumenko, Volodymyr D.; Liubich, Larysa D.; Staino, Larysa P.; Egorova, Diana M.; Vaslovych, Victoriya V.; Rozumenko, Artem V.; Komarova, Olha S.; Dashchakovskyi, Andrii V.; Kluchka, Valentin M.; Malysheva Tatyana А. (Ukrainian Neurosurgical Journal, 2023)
Objective: to study the effect of photodynamic exposure with the use of chlorine E6 in cell cultures of the standardized human glioblastoma (GB) cell line U251 under different modes of laser irradiation (LI) in vitro. Materials and methods. Groups of cell cultures of the U251 line were formed, depending on conditions of cultivation and exogenous influence: 1) control – cultivated in a standard nutrient medium (MEM with L-glutamine, 1 mml sodium pyruvate, 10% fetal calf serum) and experimental: 2) cultivated under conditions of adding a photosensitizer chlorine E6 (1.0, 2.0 and 3.0 μg/ml); 3) cultured in a nutrient medium without adding chlorine E6 and subjected to LI (intensity in the range 0.4–0.6 W, dose in the range 25–90 J/cm2, continuous or pulse mode); 4) cultivated under the conditions of adding chlorine E6 and subsequent exposure to LI in the specified modes. Intravital dynamic observation with photo-registration (fluorescence and light microscopy, survey staining methods, intravital staining with a vital dye (0.2% trypan blue solution), morphometric studies (mitotic index, numerical density of viable cells) were carried out. Results. Cell cultures of the human GB U251 line are characterized by the formation of peculiar intercellular connections (reticular histoarchitectonics) of tumor cells with high polymorphism and proliferation activity. Chlorine E6 is incorporated into the cytoplasm of U251 cells with preservation of fluorescence intensity for 72 hours (observation period). The fluorescence intensity of chlorine E6, incorporated by non-tumorally transformed cells of the rat fetal brain (E14-16), is much weaker. Under the influence of chlorine E6 (1.0, 2.0 and 3.0 μg/ml), cytodestructive processes in U251 cell culture increase in a dose-dependent manner with a progressive loss of viability and a decrease of mitotic index. After exposure to LI in the studied regimes the viability of U251 cells decreases in a dose-dependent manner already 1 h after exposure, with a further decrease after 24 h (the most significant ( 30%) – at doses of LI 75–90 J/cm2 in the pulse mode). Under the combined exposure of chlorine E6 (2.0 μg/ml) and LI, the viability of U251 cells decreases in a dose-dependent manner already 1 hour after exposure (by 4.5–10.0 times), the most significant ( 80%) – at doses of LI 75–90 J/cm2 in pulse mode. After 24 h of observation under all modes of combined exposure of chlorine E6 and LI, viable cells in U251 cultures were not detected. Conclusions. Sufficient effectiveness of the cytodestructive effect of chlorine E6 (2.0 μg/ml, preincubation for 6–24 h) and the lowest studied dose of LI (25 J/cm2) in the pulse mode in the cell culture of human GB U251 line was established. The use of vital dye provides an opportunity to record cytotoxic effects in the culture of U251 tumor cells at an early stage (within 1 h after exposure to chlorine E6 and LI).